Regulating Fintech in the CBDC Era: Addressing Competitive Fragility and Preserving State-Owned Banking Stability - Pati, Umi Khaerah; Indrajat, Heri (Journal of Indonesian Legal Studies, 2025)
This study investigates the possible consequences of Indonesia's Digital Rupiah on the future landscape of banks and FinTech companies. Our findings indicate that the advent of Central Bank Digital Currencies (CBDCs) may create an unlevel playing field between banks and FinTech firms. With the potential for intermediaries, including banks and non-bank institutions, to gain wholesale access to the Digital Rupiah, heightened competition could ensue, posing a risk to the stability of commercial banks, even extending to state-owned entities. Policymakers in Indonesia must create fair policies that promote competition among all stakeholders while strategically positioning state-owned banks to ensure economic stability and sovereignty. Drawing inspiration from Niklas Luhmann's framework of law as a social system, which emphasizes the balance between openness and closedness, and incorporating Julia Black's principle-based approach to regulation, we propose a regulatory framework and interaction pattern between bank and fintech. This framework aims to strike a balance between the needs of banks and FinTech firms by integrating elements of entity-based and activity-based regulation.